(untitled) (Fiep Bulletin - online, 2014)
The questioning is the object of analysis of this trial , as in health new teaching methods are characterized as problem-solving , PBL and problem-solving methodology ( Arch Maguerez ) . The aim of this study is to understand and analyze the strengths and weaknesses of Arch Maguerez the perspective of students and also the teachers . The methodology involves a qualitative research and data collection applied a semi - structured questionnaires and teacher discipline students disiciplina. For data analysis we used content analysis of Bardin . 20 questionnaires were applied and one semi-structured interview . The data analysis was divided into three major thematic blocks : health and illness , perception of Arch Maguerez and focus of the curriculum . These thematic shape divided into categories and subcategories that emerged from the data .